DIALOGUE OF RELIGION AND COUNTRY Actualization of Hadratussyaikh KH. Hasyim Asy'ari's Progressive Thoughts and Its Implications in The Life of The Nation and State - Toriq, Naf'an Rizal S. (State Islamic University of Datokarama Palu, 2022)
Abstract. This article discusses the dialogue between religion and the state in the perspective of Hadratussyaikh KH. Hasyim Asy'ari. The purpose of this article is to answer how is the relationship between religion and the state?, how is the relationship between Islam and Pancasila? and how is the relation between religion and religion according to Hadratussyaikh KH. Hasyim Asy'ari. This article uses a qualitative methodology whose primary data is more specifically obtained from the works of Hadratussyaikh, while the secondary data is in the form of journals, books, field notes or others that are still related to the research theme. The data collection uses documentation techniques, namely by examining the thoughts/ideas of Hadratussyaikh in several of his works. While the data analysis used descriptive analysis. Based on the observations of researchers, the relationship between religion and the state according to Hadratussyaikh is grouped into three things, namely; First, the relationship between religion and the state is divided into three, namely integralistic, secularistic and symbiotic. Second, the relationship between Pancasila and Islam is very closely related, especially when viewed from the first precept which contains the meaning of monotheism or monotoism. Third, the existence of religion in a community functions as a protector, protector and helper for the benefit of the ummah. Seeing this typology, the role of religion and the state is symbiotic. Hadratussyaikh did not mention in a sharih manner the state system must be Islamic or other systems, but he strongly emphasized the existence of an Islamic spirit which was implemented in the form of principles or ethics in life (social-politics).